Pecalang, Cultural Governance, and Immigration Control: Community Resilience in The Traditional Village of Canggu - Mochamad Irsyad Makrufi; Stanislaus Riyanta (International Journal of Science and Environment (IJSE), 2026)
This study examines the role of Pecalang in the social surveillance of foreigners in Canggu Traditional Village, Bali, and its integration with local cultural governance and the formal immigration system. Using a non-interview qualitative approach based on administrative data from the Ngurah Rai Class I Special TPI Immigration Office, this study documents the dynamics of community-based social oversight in the context of globalization, international migration, and global tourism. Data on administrative immigration actions specifically deportations and enforcement measures against foreign nationals were obtained directly from the Immigration Office for the period 2024–2025. The findings reveal that Pecalang performs an adaptive function beyond securing traditional ceremonies, acting as a social monitor of the activities of tourists, digital nomads, and foreign investors. This function is reinforced through collaboration with immigration authorities, enabling early detection of potential legal and social violations. The integration of awig-awig (customary law) and formal regulations creates a synergy of community-based oversight that enforces socio-customary norms while ensuring compliance with national laws. The study also highlights the challenges posed by conflicting interests between tourism development and cultural preservation. Administrative data from Ngurah Rai Immigration Office shows a total of 300 deportation/administrative actions in 2024 and 337 in 2025 a 12.3% increase indicating growing immigration enforcement activity in Bali. These local mechanisms contribute significantly to community resilience, enabling communities to adapt to external changes without losing their cultural identity. Based on empirical findings, the study develops a conceptual model of community-based immigration oversight emphasizing early detection, preventive supervision, and enforcement of socio customary norms through collaboration among Pecalang, Traditional Villages, and formal authorities